Efficacy of antimalarial drug treatments for uncomplicated falciparum and vivax malaria in selected Southeast Asian countries: A meta-analysis - Lurzano, Jed Arvin S. (Animo Repository, 2023)
Antimalarial treatment varies extensively as its success is attributed to numerous factors such as patient’s health, comorbidities, infecting species, geographical region, and more. While the global malaria rate has been steadily decreasing, developing Southeast Asian countries are still at risk, especially with the decreasing efficacy of current antimalarial drugs due to drug resistance. This meta-analysis initially selected eight Southeast Asian countries, which were then finalized into five countries that had optimal data (Cambodia, Indonesia, Myanmar, Thailand, and Vietnam). Sixteen studies from these countries were selected to assess the efficacy of antimalarial treatments against Plasmodium falciparum and Plasmodium vivax. From the combination treatments, triple-based combination drug therapies have a higher relative mean efficacy compared to double-drug combinations. Against P. vivax, a t-test showed that Dihydroartemisinin-Piperaquine (DHA-PPQ) is superior compared to Chloroquine (CQ) alone (p < .001). Meanwhile, the mean efficacy of the drug therapies against P. falciparum was found to have a significant difference among the ten treatment groups (p < .001). The modified Tukey’s test formed four homogenous groups, and the group that had the highest mean efficacy against P. falciparum consisted of the following: Dihydroartemisinin-Piperaquine plus Artesunate (DHA-PPQ + AS), Dihydroartemisinin-Piperaquine plus Mefloquine (DHA-PPQ + MQ), Pyronaridine-Artesunate (PYN-AS), Artemether-Lumefantrine plus Amodiaquine (AL + AQ), and Pyrimethamine-Artesunate (PYR-AS). The mean age and treatment efficacy do not have any correlation (p = 0.1345). A t-test was performed to compare the efficacy of antimalarial drugs in the Thailand-Cambodia area in contrast to both Thailand and Cambodia. The results show that drug efficacy in the Thailand-Cambodia border is significantly lower (p < .001), which is attributed to the emergence of multidrug-resistant Plasmodium species in the area.